Unveiling the realities of STEM integration in biology: Teachers' perceptions, challenges, and classroom practices in Indonesia - M. Eval Setiawan; Wilda Purnawati; Muhammad Saefi; Betaria Putra; Defita Permata Sari; Widi Cahya Adi; Dedy Dwi Putra; Futri Zakiah Apria Sapawer; Noviansyah Kusmahardhika (University of Muhammadiyah Malang, 2026)
Background: Although STEM plays a critical role in biology education, a persistent disconnect exists between Indonesian teachers' strategic knowledge and their pedagogical practices. Objectives: This study sought to examine biology teachers’ perceptions of STEM, their knowledge of implementation strategies, and their understanding of implementation challenges. Additionally, it assessed the gap between teachers’ strategic knowledge and classroom practices. Methods: A mixed-methods design employing a sequential explanatory approach was utilised, consisting of a quantitative survey of 94 high school biology teachers (purposive sampling), followed by semi-structured interviews. The 16-item instrument demonstrated reliability (Cronbach's α = 0.878). Quantitative data were analysed descriptively (means and standard deviations), while qualitative data were analysed thematically, utilising triangulation and member checking. Results: Teachers exhibited high knowledge of STEM implementation strategies (M = 4.22 ± 0.75), but reported moderate barriers to implementation (M = 3.62 ± 0.78), moderate self-confidence (≈ M = 3.16), and moderate to high STEM teaching practices (M = 3.52 ± 0.77). Interviews revealed that STEM was frequently defined as simple technology use; however, components such as engineering design, modelling, meaningful mathematics, and performance assessment were inconsistently applied, largely due to limitations in training, time, facilities, and access to technology. Conclusion: Practice-based professional development, a unified STEM framework for biology, and school support–including project time blocks and low-cost tools–are essential for translating knowledge into consistent classroom practice.